If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Senx = 3cosx Solving enxS = 3cosx Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Divide each side by 'nxS'. e = 3cn-1osS-1 Simplifying e = 3cn-1osS-1
| v/10=11/7 | | X(3)=-15 | | 3x+2x-1=15 | | -5*-5=25 | | 4x^4-85x^2+441= | | 5=17-3x | | 2(12-x)=216 | | 3x+y=2x+3 | | 2y/3y-2 | | 36=4/x | | 60x=5+x | | 0=6sqrtx-x | | 2axy-8axy= | | 36=x/4 | | 3(1+6+2(5+2))= | | 3/4h=-14 | | 16x+-156=8x+-92 | | M7/m5= | | 5x^3-14x^2+5x-24=0 | | 5y-2x=23x-10 | | 16+3=3(5x-2)+9 | | x+5x-110=550 | | 3+9lnx=2 | | -r=-x+dt | | -20x-7y=15 | | R=-x+dt | | 6-z=2 | | 5y+15*y+1=35 | | 3.5x=10 | | 2x^2+7x+3=30 | | 5x-4x=-2x(3x+2) | | 7-v(4v+1)=0 |